Fine needle aspiration cytology in head and neck masses, assessment of need for incision/excision biopsy - Yenkure, Priyanka; Pore, Shubhajyoti; Joshi, Anil; Kaur , Damandeep (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: FNAC is a rapid, simple, cost-effective, and minimally invasive technique used to diagnose different types of swelling occurring in head and neck masses, and assess its need for biopsy. Methods: The study included 650 patients, who presented with palpable head and neck swelling over a period of 18 months, at our hospital. FNAC procedure has been performed and smears are stained with Papanicolaou stain, Gemisa stain, and H and E stain. Cyto-histopathological correlations were done to evaluate the need for a biopsy. Results: Out of 650 cases, lymph node lesions constitute 370 cases (56.90%) most commonly involved. Thyroid gland lesions constitute 189 cases (29.10%) followed by salivary gland lesions 38 cases (5.80%), and other 53 cases (8.20%). Histo-pathological correlation of 116 cases were done out of 650. Conclusions: FNAC serves as a guide to appropriate therapeutic management whether to locally excise a benign tumor or plan radical surgery and helps as an adjunct to histopathology.